Implementation of Social Welfare Based on the Welfare State Theory : Case Study on the Provision of Social Assistance Funds During COVID-19 in Indonesia - Aprilian Ismail Nurahsan; Wicipto Setiadi; Taufiqurrohman Syahuri (International Journal of Law and Society, 2025)
This research examines the implementation of social welfare through social assistance funds in Indonesia during the Covid-19 pandemic within the framework of the welfare state theory. Using a normative juridical approach with a descriptive-normative character, the study analyzes the legal foundations, the theory of justice, and utilitarianism as conceptual bases. Two approaches Statute Approach and Conceptual Approach are employed to review key regulations (Law No. 13/2011, Law No. 11/2009, Government Regulation No. 39/2012, and other implementing regulations) as well as the concepts of distributive justice, utility, and the capability principle. Secondary data consists of primary, secondary, and tertiary legal materials collected through literature study and qualitatively analyzed. The findings reveal that programs such as Direct Cash Assistance (BLT), the Family Hope Program (PKH), and the Staple Food Card (Kartu Sembako) represent state interventions aimed at correcting inequality and ensuring citizens’ social rights. The application of the principles of social justice, utility, transparancy, accountability, participation, and sustainability has strengthened the legitimacy of social assistance as a redistributive instrument. However, the main challenges lie in the accuracy of the Integrated Social Welfare Data (DTKS), overlapping recipients, limited public participation, and long-term planning that remains reactive to crises. Evaluation of alignment with welfare state principles reveals that social assistance interventions have helped reduce short-term economic burdens but are not yet optimal in empowering recipients toward self-reliance. Based on these findings, it is recommended to regularly update the DTKS, enhance digitalization and data transparancy, expand participatory mechanisms, and integrate social assistance policies into long-term national development strategies. Thus, social assistance funds can serve not only as emergency aid but also as sustainable instruments to realize social justice and inclusive growth.